Sonographic Evaluation of Plantar Fasciitis and its Relation to Body Mass Index and Heel Pad Thickness - Khatiwada, Prashant; Chataut, Dinesh; Subedi, Kamal (Nepalese Journal of Radiology, 2020)
Introduction: To study the sonographic appearance of plantar fascia in clinically suspected cases of plantar fasciitis (PFs) using both quantitative and qualitative parameters, and to establish the correlation between plantar fasciitis, body mass index (BMI) and heel pad thickness (HPT). Methods: In this case controlled analytical study, we sonographically evaluated 100 patients with clinical plantar fasciitis (unilateral: 90, bilateral: 10 with mean age 46.9yrs) and control group of 60 (120 heels) healthy volunteers with mean age 45.3yrs. Plantar Fascia Thickness (PFT), HPT, hypoechogenity, biconvexity, perifascial fluid, intrafascial calcification and subcalcaneal spurs were evaluated sonographically. PFT was measured 5mm distal to the calcaneal insertion of plantar aponeurosis. The unloaded HPT was measured from the skin surface to the nearest calcaneal tuberosity. Results: Mean Plantar Fascia Thickness (PFT) and Heel Pad Thickness (HPT) are greater on the symptomatic side for patients with unilateral and bilateral PFs than on the asymptomatic side for patients with unilateral PFs, and also control subjects (PFT values are 4.41 ± 0.59, 4.63 ± 0.55, 2.83 ± 0.36, 2.62± 0.37 mm, and HPT values 17.64 ± 1.07, 17.28 ± 1.10, 16.91 ± 1.06, 16.73 ± 1.13 mm, respectively) (p <0.0001). Mean BMI values of the case and control groups are 26.14 ± 1.9 and 24.42 ± 0.89 Kg/m2, respectively (p <0.05). We found hypoechogenicity of plantar fascia in 80 cases (72.7%), calcaneal spur in 69 cases (62.7%), biconvexity in 11 cases (10%) and perifascial fluid in 16 cases (14.5%) within the plantar fasciitis group (110 symptomatic heels). Conclusion: Increased plantar fascia thickness, increased heel pad thickness and hypoechogenicity of plantar fascia are consistent sonographic findings in plantar fasciitis. Its occurrence has significant relation to high BMI.